2007
DOI: 10.1183/09031936.00036307
|View full text |Cite|
|
Sign up to set email alerts
|

Airway dendritic cell phenotypes in inflammatory diseases of the human lung

Abstract: Airway dendritic cells (DCs) are key regulators of pulmonary immune responses. However, information is limited regarding the characteristics of airway DCs in human lung diseases.Plasmacytoid DCs (pDCs) and myeloid DCs (mDCs) were analysed using four-colour flow cytometry in bronchoalveolar lavage fluid (BALF) from nonsmoking controls and patients with sarcoidosis, idiopathic pulmonary fibrosis (IPF) and pneumonia (in the presence or absence of immunosuppression).Compared with controls, immunocompetent patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 35 publications
(61 reference statements)
3
87
1
Order By: Relevance
“…As shown in Figure 7, iloprost downregulated poly I:C-induced H3K4 trimethylation in the TNFA gene promoter region from upstream to downstream of the transcription start site ( Figure 7A). Be- cause histone trimethylation is mediated by methyltransferase, we next examine whether the downregulation of H3K4 trimethylation by iloprost is associated with the downregulation of the H3K4-specific methyltransferases and MLL and WDR5 proteins (9). Intriguingly, poly I:C-induced translocation of MLL and WDR5 protein from cytoplasm into nucleus, and iloprost, can partly reversed the translocation of MLL and WDR5 proteins from cytoplasm to nucleus by poly I:C (Figures 7B, D).…”
Section: Iloprost Suppressed Poly I:c-induced Tnf-α Expression Via Himentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 7, iloprost downregulated poly I:C-induced H3K4 trimethylation in the TNFA gene promoter region from upstream to downstream of the transcription start site ( Figure 7A). Be- cause histone trimethylation is mediated by methyltransferase, we next examine whether the downregulation of H3K4 trimethylation by iloprost is associated with the downregulation of the H3K4-specific methyltransferases and MLL and WDR5 proteins (9). Intriguingly, poly I:C-induced translocation of MLL and WDR5 protein from cytoplasm into nucleus, and iloprost, can partly reversed the translocation of MLL and WDR5 proteins from cytoplasm to nucleus by poly I:C (Figures 7B, D).…”
Section: Iloprost Suppressed Poly I:c-induced Tnf-α Expression Via Himentioning
confidence: 99%
“…DCs play a major role in initiation and regulation of adaptive immune responses to the stimulation of antigens and allergens (9). In a murine asthma model, myeloid dendritic cells (mDCs) accumulate in the allergen-challenged airways during the acute phase, and the depletion of mDCs attenuates the airway inflammation and hyperresponsiveness (10).…”
Section: Introductionmentioning
confidence: 99%
“…In studies applying more advanced flow cytometry panels, noncancerous lung tissue from surgical resections of patients were typically used (14,(26)(27)(28), although it is unclear whether these rare populations are truly representative of DCs present in healthy subjects. Indeed, several studies have investigated DCs in the context of lung diseases such as asthma, chronic obstructive pulmonary disease, bronchiolitis, and sarcoidosis (29)(30)(31)(32)(33)(34)(35). In chronic obstructive pulmonary disease, the expression of maturation molecules on DCs has been proposed as a potential diagnostic/therapeutic target.…”
mentioning
confidence: 99%
“…Havenith et al, 1993;Xia et al, 1995): within 12 hours, the lung derived DCs can be found in the T-cell area of draining mediastinal lymph nodes of the lung. Inflammatory diseases of the human lung are associated with the different phenotypes and the process of the recruitment of the airway DCs (Lommatzsch et al, 2007(Lommatzsch et al, , 2010Geurtsvankessel and Lambrecht, 2008;Vassallo et al, 2010). Regulation of galectin-3 in the lungs may represent one of the multiple potential mechanisms by which galectins contribute to modulation of the innate and acquired immune responses (Maldonado et al, 2011).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Highly specialized and notably heterogenous, DCs function as messengers and regulators between innate and acquired immunity (e.g. Reid, 1997;Hart, 1997;Banchereau and Steinman, 1998;Austyn, 1998;Satthaporn and Eremin, 2001;Dzionek et al, 2000;Webb et al, 2005;McKenna et al, 2005;Lommatzsch et al, 2007Lommatzsch et al, , 2010GeurtsvanKessel and Lambrecht, 2008;von Garnier and Nicod, 2009). Because DCs have the ability to induce a primary immune response in resting naïve T-lymphocytes and play a role in the maintenance of B-cell function and antigen memory (recall) responses (e.g.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%